Analyzing the Relationship between Personal Hygiene, Environmental Sanitation, and Soil-Transmitted Helminth (STH) Worm Infection among Children Aged 3-8 Years in Oesena Village, Amarasi District, Kupang Regency, East Nusa Tenggara - Agustina W. Djuma; Agustina M. V. Saga; Aldiana Astuti; Yuanita C.L. Rogageli (Nusantara Science and Technology Proceedings, 2023)
Soil-transmitted helminths refer to the intestinal worms infecting humans that are transmitted through contaminated soil and most commonly infect children. The purpose of this study was to investigate risk factors for STH worm infection in children aged 3-8 years in Oesena Village, Amarasi District, Kupang Regency. The type of study used is an observational analysis study with a cross-sectional study design. The sample size for this study was 68 of simple random sampling was selected. Data on helminthiasis were obtained from stool examinations using native methods, whereas data on personal and environmental hygiene were collected by questionnaire interviews and observations. Data were analyzed using the chi-square test and proceeded to calculate the prevalence (RP). Twelve patients (17.6) were infected with STH as a result of stool examination. 14.6% were infected with Ascaris lumbricoides, 1.5% with Strongyloides stercolaris, and 1.5% with hookworm. Personal hygiene at risk for his STH worm infection of her 3 to 8-year-old child in Oesena village, Amarasi district, Kupang district, played on the floor with a prevalence (RP) of 10.37. This includes the habit of washing your hands afterward and wearing your shoes. PR = 9.78, nail clipping habit PR = 3.23. Risk Probability for STH worm infection in children aged 3-8 years in Oesena Village, Amarasi District, Kupang Regency, East Nusa Tenggara Province include Personal Hygiene were habit of washing hands after playing on the ground, Habit of wearing footwear, and Habit of cutting nails.